Preparation and characterization of PEG-coated silica nanoparticles for oral insulin delivery - Andreani, Tatiana; Souza, Ana Luiza R. de [UNESP]; Kiill, Charlene P. [UNESP]; Lorenzon, Esteban N. [UNESP]; Fangueiro, Joana F.; Cristina Calpena, Ana; Chaud, Marco V.; Garcia, Maria L.; Gremiao, Maria Palmira D. [UNESP]; Silva, Amelia M.; Souto, Eliana B. (Elsevier B.V., 2014)
The present study reports the production and characterization of PEG-coated silica nanoparticles (SiNP-PEG) containing insulin for oral administration. High (PEG 20,000) and low (PEG 6000) PEG molecular weights were used in the preparations. SiNP were produced by sol gel technology followed by PEG adsorption and characterized for in vitro release by Franz diffusion cells. In vitro permeation profile was assessed using everted rat intestine. HPLC method has been validated for the determination of insulin released and permeated. Insulin secondary structure was performed by circular dichroism (CD). Uncoated SiNP allowed slower insulin release in comparison to SiNP PEG. The coating with high molecular weight PEG did not significantly (p>0.05) alter insulin release. The slow insulin release is attributed to the affinity of insulin for silanol groups at silica surface. Drug release followed second order kinetics for uncoated and SiNP PEG at pH 2.0. On the other hand, at pH 6.8, the best fitting was first-order for SiNP PEG, except for SiNP which showed a Boltzmann behavior. Comparing the values of half-live, SiNP PEG 20,000 showed a faster diffusion followed by Si-PEG 6000 and SiNP. CD studies showed no conformational changes occurring after protein release from the nanoparticles under gastrointestinal simulated conditions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Silica nanoparticles; Insulin; PEG adsorption; Oral delivery; Mathematic modeling; HPLC validation